The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2164-14-621
|View full text |Cite
|
Sign up to set email alerts
|

Leaf cDNA-AFLP analysis of two citrus species differing in manganese tolerance in response to long-term manganese-toxicity

Abstract: BackgroundVery little is known about manganese (Mn)-toxicity-responsive genes in citrus plants. Seedlings of ‘Xuegan’ (Citrus sinensis) and ‘Sour pummelo’ (Citrus grandis) were irrigated for 17 weeks with nutrient solution containing 2 μM (control) or 600 μM (Mn-toxicity) MnSO4. The objectives of this study were to understand the mechanisms of citrus Mn-tolerance and to identify differentially expressed genes, which might be involved in Mn-tolerance.ResultsUnder Mn-toxicity, the majority of Mn in seedlings was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 113 publications
2
39
0
Order By: Relevance
“…Guo et al (2014) reported that B-toxicity induced the expression of ABC transporter G family 40 in 'Sour pummelo' leaves. However, the expression of two ABC transporter genes (i.e., TDFs #62-1 and 127-2) was detected only in ÀAl leaves (Table 1), which agrees with the results obtained on Mn-toxic 'Sour pummelo' leaves (Zhou et al, 2013). showed that upregulation of an Mg transporter gene OsMGT1 was required for conferring rice Al-tolerance.…”
Section: Transport Genessupporting
confidence: 90%
See 2 more Smart Citations
“…Guo et al (2014) reported that B-toxicity induced the expression of ABC transporter G family 40 in 'Sour pummelo' leaves. However, the expression of two ABC transporter genes (i.e., TDFs #62-1 and 127-2) was detected only in ÀAl leaves (Table 1), which agrees with the results obtained on Mn-toxic 'Sour pummelo' leaves (Zhou et al, 2013). showed that upregulation of an Mg transporter gene OsMGT1 was required for conferring rice Al-tolerance.…”
Section: Transport Genessupporting
confidence: 90%
“…qRT-PCR analysis was performed according to Zhou et al (2013). There were three biological replicates and two technical replicates for each treatment.…”
Section: Qrt-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of OsCBSX4 improved tobacco plant tolerance to salinity, oxidative, and heavy metal stresses [43]. We observed that B-toxicity decreased the transcript level of CDCP (TDF #251_3) in C. sinensis leaves (Table 2), as obtained on manganese (Mn)-toxic C. grandis leaves [44]. However, B-deficient C. sinensis roots had higher level of CBS family protein [45].…”
Section: Discussionmentioning
confidence: 98%
“…There were three biological replicates. cDNA synthesis, purification and cDNA‐AFLP analysis were performed according to Zhou et al …”
Section: Methodsmentioning
confidence: 99%